2022
DOI: 10.1001/jamasurg.2021.6900
|View full text |Cite
|
Sign up to set email alerts
|

Patient Factors Associated With Appendectomy Within 30 Days of Initiating Antibiotic Treatment for Appendicitis

Abstract: Writing Group for the CODA Collaborative IMPORTANCE Use of antibiotics for the treatment of appendicitis is safe and has been found to be noninferior to appendectomy based on self-reported health status at 30 days. Identifying patient characteristics associated with a greater likelihood of appendectomy within 30 days in those who initiate antibiotics could support more individualized decision-making. OBJECTIVETo assess patient factors associated with undergoing appendectomy within 30 days of initiating antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The CODA trial 22 reported complications in 14 per cent of participants randomized to antibiotic therapy with an appendicolith compared with only 2 per cent of those without an appendicolith. Thus, it may be that this large trial (approximately of a size equal to all the other trials combined) and its inclusion of participants with appendicoliths has affected the analysis significantly, particularly as a secondary analysis of the trial found that presence of an appendicolith was associated with a nearly two-fold increased risk of participants undergoing an appendicectomy within 30 days of initiating antibiotic treatment 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The CODA trial 22 reported complications in 14 per cent of participants randomized to antibiotic therapy with an appendicolith compared with only 2 per cent of those without an appendicolith. Thus, it may be that this large trial (approximately of a size equal to all the other trials combined) and its inclusion of participants with appendicoliths has affected the analysis significantly, particularly as a secondary analysis of the trial found that presence of an appendicolith was associated with a nearly two-fold increased risk of participants undergoing an appendicectomy within 30 days of initiating antibiotic treatment 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Appendectomy has been recognized as a standard treatment for appendicitis for a long time. Nevertheless, the successful management of patients without surgery is evident in several studies [ 24 , 25 ]. One of the most recent studies suggests that female sex, appendiceal diameter, and the presence of an appendicolith are factors that result in increased odds of having to undergo an appendectomy compared to using antibiotic treatments [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The process of making a balanced judgement on whether to perform an appendectomy or not remains very challenging, mainly due to the variation in symptoms and signs in different patients, but also due to the lack of standardized care and organizational barriers [ 25 ]. That being said, there are several reasons why the insights derived from this study are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Total serious morbidity-modified National Surgical Quality Improvement Program (NSQIP) events were documented in 3.5% of patients randomized to surgical intervention in the 2020 Comparison of Outcomes of Antibiotic Drugs and Appendectomy (CODA) Trial. In 2015, the overall (not just serious) complication rate was 20.5% in the Finnish Antibiotic Therapy vs Appendectomy for Treatment of Uncomplicated Acute Appendicitis (APPAC) study [ 15 , 20 , 36 ]. An aggregated incidence of postoperative complications in a mixed population including uncomplicated and complicated appendicitis of 18.4% was derived from a meta-analysis of eleven trials assessing 1288 patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%